2007
DOI: 10.1029/2006jd007320
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentration and speciation in the coastal and open ocean boundary layer

Abstract: [1] Atmospheric elemental mercury and reactive gaseous mercury (RGHg) concentrations, as well as ancillary parameters and meteorological data, were collected during a cruise in the North Atlantic Ocean between Bermuda and Barbados and at two land-based sites: the Chesapeake Biological Laboratory (CBL), a semirural, coastal site, and a site within the city of Baltimore, Maryland. There were two deployments at CBL, including a 6-month deployment in 2003/2004. Wet deposition samples were collected and analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
75
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 64 publications
16
75
3
Order By: Relevance
“…Sigler et al (2009a, b) and Mao and Talbot (2011) observed RGM depletion during precipitation events at this site and others have made similar observations at diverse locations (Lindberg and Stratton, 1998;Yatavelli et al, 2006;Laurier and Mason, 2007). Despite this indication of RGM scavenging during precipitation events at TF, correlations between Hg wet deposition and Hg concentration in precipitation versus daily maximum RGM and RGM depletion during precipitation events were not statistically significant (Table 2).…”
Section: Scavenging Of Rgm During Precipitation Eventsmentioning
confidence: 67%
“…Sigler et al (2009a, b) and Mao and Talbot (2011) observed RGM depletion during precipitation events at this site and others have made similar observations at diverse locations (Lindberg and Stratton, 1998;Yatavelli et al, 2006;Laurier and Mason, 2007). Despite this indication of RGM scavenging during precipitation events at TF, correlations between Hg wet deposition and Hg concentration in precipitation versus daily maximum RGM and RGM depletion during precipitation events were not statistically significant (Table 2).…”
Section: Scavenging Of Rgm During Precipitation Eventsmentioning
confidence: 67%
“…Changbai (Wan et al, 2009 , n ¼ 50) (ttest, p < 0.01). The mean concentration of RGM during the entire study period was 3.3 ± 2.3 pg m À3 (n ¼ 110), which was comparable to the global mean concentration of RGM in the MBL (Soerensen et al, 2010), and somewhat higher than those of rural or coastal areas in North America (Table 1), such as the Ontario Lake (Cheng et al, 2012), several coastal sites in Nova Scotia (Cheng et al, 2013a(Cheng et al, , 2014, and slightly lower than those of other seas, such as the Mediterranean Sea , the Weeks Bay (Engle et al, 2008), the Adriatic Sea (Sprovieri and Pirrone, 2008), the subtropical North Atlantic (Laurier and Mason, 2007), the Okinawa Island (Chand et al, 2008), and the North Pacific Ocean (Laurier et al, 2003). But RGM concentrations measured in this study area were much lower than those of urban or rural sites in China and South Korea, such as Guiyang Liu et al, 2011), Xiamen (Xu et al, 2015), Mt.…”
Section: Quality Assurance and Quality Controlmentioning
confidence: 81%
“…The mean GEM concentration during spring (2.03 ± 0.72 ng m À3 , n ¼ 5243) was comparable to that during fall (2.09 ± 1.58 ng m À3 , n ¼ 4413) (t-test, p > 0.05). The mean GEM level during the whole study period was 2.07 ± 1.16 ng m À3 , which was higher than those in some other open oceans (see Table 1), such as the Atlantic Ocean (Laurier and Mason, 2007;Soerensen et al, 2013), the equatorial Pacific Ocean (Soerensen et al, 2014), the Adriatic Sea (Sprovieri and Pirrone, 2008), and the Indian Ocean (Witt et al, 2010), even higher than those of rural coastal sites in Canada (Cheng et al, 2014), and was comparable to those of coastal sites, such as the Hedo Station (Chand et al, 2008) in Japan, and the Augusta basin (Bagnato et al, 2013) in Italy, but lower than those reported in the northern South China Sea (Fu et al, 2010;Tseng et al, 2012 Fig. 3).…”
Section: Quality Assurance and Quality Controlmentioning
confidence: 95%
See 2 more Smart Citations